Recent research on liver fibrosis and cirrhosis - LU Lungen (Linchuang Gandanbing Zazhi, 2013)
Liver cirrhosis can do great harm to human health due to irreversible function impairment of hepatocytes and severe complications caused by portal hypertension. Liver fibrosis is an inevitable stage through which chronic liver disease progresses to cirrhosis. So far, most studies have demonstrated that the liver disease in fibrosis stage can be reversed. This paper reviews recent research on liver fibrosis and cirrhosis.